Immunostimulants in the prevention of respiratory infections. - Río Navarro, Blanca del; González Díaz, Sandra Nora; Escalante Domínguez, Alberto José; Blandón Vijil, María Virginia (Inderscience Enterprises, 2007)
ABSTRAC Immunomodulation promises to be an effective prophylactic and therapeutic modality for chronic and recurrent respiratory infections. As opposed to vaccines, the term Immunostimulant (IS) refers to a compound that produces a state of non-specific immunity. Most IS are oral formulations of bacterial lysates that have been used in clinical practice for decades. One of the main obstacles in the development of immunostimulants is the poor understanding of the mechanism of action. Except for some compounds the mechanism of action of bacterial products is not well understood.